Contribution of Milk components on Protein Aggregation - Lor, Kong Peng (East Carolina University, 2021)
Protein aggregation is a known health hazard that has been implicated in more than 50 human diseases. These diseases have been linked to lifestyle as they mostly prevail in the western world. Besides environmental factors food is an important part of lifestyle. Metal exposure inducing human diseases is well known. And many food products are very rich in metals. Further, many foods are fortified with metal atoms like Ca2+. We took it upon ourselves to explore the effect of components of food on protein aggregation using a model protein BSA. Further, we chose to explore the effect of components of milk on BSA aggregation because milk is consumed universally. We chose monovalent and divalent metal ions like Ca2+, Mg2+ and K+ and also non-metal component of milk like lactose. We used biophysical techniques like light scattering, ThT fluorescence, Bradford's protein essay, gel electrophoresis, electron micrography and size exclusion chromatography in this project. The light scattering experiments showed both metal and non-metal components at the concertation present in the biological cow milk or physiological levels was able to induce aggregation in BSA under the conditions studied here. That the aggregating was happening under our conditions was further supported by Bradford assay, EM analysis and size exclusion chromatography data. Surprisingly, ThT assay that is widely used for amyloid aggregation assay did not show the data in line with the above-described methods. While the ThT fluorescence should have increased it decreased but did not completely flatten out. We believe there is a dynamic process between the aggregating BSA molecules, the metal or non-metal additive molecules and ThT molecules interplaying with each other and that finally results in decreased ThT fluorescence. Out of the additives Mg2+ and Ca2+ appeared to enhance the BSA aggregation most and we propose that is because they are able to interact with the acidic amino acids of the BSA molecule. K+ and lactose appears to exert their influence through the solvent rearrangement (chaotropic or kosmotrophic effect). The studies we will try to describe here will have relevance to human health and diseases.
Keywords: Protein aggregation; BSA; Proteins--Conformation; Protein folding; Milk--Microbiology; Metals--Toxicology